The Analysis of Factors Affecting Stock Prices in Cigarette and Toobaco Companies Listed on the Indonesia Stock Exchange - Kusmayadi, Kusmayadi; Dewi Sri Marsanti; Didiek Susilo Tamtomo; I Nyoman Romangsi; Sulistiyo, Sulistiyo (Cita konsultindo, 2023)
This research has the aim to test the truth of Return On Equity (ROE), Earning Per Share (EPS), and Net Profit Margin (NPM) giving a simultaneous or partial effect on stock prices. In this research, the value of the company/company is proxied using Price to Book Value (PBV). This research uses a population of 5 Cigarette and Toobaco companies on the IDX list during the 2017-2021 period. Materials/data for the acquisition test are sourced from the financial report notes issued by the IDX. The sampling procedure uses a purposive sampling method that only uses Cigarette and Toobaco companies that are listed in succession during the 2017-2021 period, publishes historical stock prices during the research period, and does not experience losses during the research period. The number of samples that passed the category was 5 Cigarette and Toobaco companies which were studied for 5 years so the observation data were 25 observations. The results of the Coefficient of Determination in this study, which can be observed in Adjusted R Square, have a score of 42,9%. Stock prices can be influenced by ROE, EPS, and NPM, while the remaining 57,1% are influenced by other aspects that are not included in the study. Keywords : Earning per share, Return on Asset, Return on Equity, Net Profit margin, Stock Price